From Student to Teacher: Renegotiating Professional Identities - Zachary Milford; Anne Corey Reed (Educational Considerations, 2024)
This case-study examines how first-year educators renegotiated their teacher identities as they transitioned from pre-service teachers (PSTs) to professionals. Both participants graduated from the same Teacher Education Program (TEP) and conducted their student internship in the same school as their first year of teaching. The results of this study have unique implications on first-year teachers working in the location of their student internships, as they reported isolation, internalized infantilization, and inconsistent identities. The author argues for TEPs to intentionally prepare PSTs for navigating this transition, and challenge preconceived notions of the benefits of student teaching and working in the same K-12 institution.
Keywords: Teacher Identity; Preservice Teacher; Case Study; Dialogism